Arbeiderbevegelsens arkiv og bibliotek 1908-2025: Historisk kulturarv og samfunnsdigitalisering - Rønning, Ole Martin (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2025)
This article examines the development of the Norwegian labour movement’s archives and library in oslo (Arbark) from its establishment in 1908 to the present day. The text describes and analyses the archive within a changing social context and focuses on the intentions of the owners, the Norwegian Labour Party and the Confederation of Trade Unions, as well as the archive’s own ambitions, and tries to identify factors that have been decisive at important crossroads of change. The article also highlights current challenges and solutions related to the general digitalization of society that has taken place over the past few decades.